Extraction method for manipulation of water- and organic-soluble extracts of PM2.5 in Korean winter season and its chemical composition - Shin, C.-Y.; Park, H.-M.; Park, K.-S.; Lee, S.-B.; Lee, H.S.; Jung, H.; Kim, Y.-J.; Ryu, J.-C. (2013)
Particulate matter (PM) air pollution is a significant environmental issue. PM is divided into three main fractions based on its size: coarse (2.5-10 μm), fine (0.1-2.5 μm), and ultrafine fractions (<0.1 μm). Fine particles and ultrafine fractions which are designated as particulate matter 2.5 (PM2.5) is small enough to reach alveoli in the lungs. Although the correlation between the chemical composition of PM2.5 and its toxic mechanisms has not been elucidated, several studies of PM2.5 have found evidence that ambient air PM2.5 is associated with adverse health effects. In the present study, the chemical compositions of water- and organic-soluble extracts of PM2.5 from 50 sample filters collected in the winter in the middle part of Seoul were measured. The water-soluble extract was analyzed to determine its contents of inorganic ions and metals using ion chromatography, atomic absorption spectrometry, and inductively coupled plasma-atomic emission spectrometry. The main inorganic ions were Cl-, NO3 -, SO4 2-, and NH4 +, with a total quantity in the range of 20.02 to 40.22 μg/m3 in ambient air. In a sample of all five groups, Na, K, Ca, Mg, Cd, Cr, Cu, Fe, Mn, Ni, V, and Zn together accounted for 902.14 to 1631.25 ng/m3 in ambient air. The concentrations of thirteen polycyclic aromatic hydrocarbons (PAHs) in the organic-soluble extract were analyzed using gas chromatography/time of flight-mass spectrometry. The thirteen PAHs combined constituted 6.24-76.05 ng/m3 in ambient air. In this study, we report the chemical composition of PM2.5 during the winter season in Seoul and suggest using a high-volume air sampler to create water- and organic-soluble extracts from large amounts of PM2.5, which could be used to conduct in vitro and in vivo experiments, including studying genomic changes following PM exposure. ？ 2013 Korean Society of Environmental Risk Assessment and Health Science and Springer Science+Business Media Dordrecht.
Keywords: acenaphthylene; ammonia; anthracene; benz [a] anthracene; benzo [b] fluoranthene; benzo [ghi] perylene; benzo [k] fluoranthene; benzo[a]pyrene; cadmium; calcium; chloride ion; chromium; chrysene; copper; dibenz [a, h] anthracene; fluoranthene; indeno [1, 2, 3 cd] pyrene; iron; magnesium; manganese; nickel; nitrate; phenanthrene; potassium; pyrene; reactive oxygen metabolite; sodium; sulfate; unclassified drug; vanadium; zinc; article; atomic absorption spectrometry; atomic emission spectrometry; chemical analysis; chemical composition; controlled study; extraction; ion pair chromatography; particulate matter; priority journal; South Korea; time of flight mass spectrometry